1978
DOI: 10.1016/s0006-3495(78)85393-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative rates of repair of single-strand breaks and postirradiation DNA degradation in normal and induced cells of Escherichia coli

Abstract: Labeled DNA from irradiated Excherichia coli cells has been studied on an alkaline sucrose gradient without acid precipitation of the DNA. This enables the observation of both DNA repair and DNA degradation. The use of a predose of ultraviolet light (UV) causes induction of an inhibitor of postirradiation DNA degradation in lex+ strains. The effect of this induction on both the repair of single-strand breaks and DNA degradation has been followed in strains WU3610 (uvr+) and WU3610-89 (uvr-). The repair process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is well known that treatment of cells with one DNA damaging agent, followed by incubation in growth conditions, makes them better prepared to repair DNA lesions from subsequent exposures to different DNA damaging treatments (216, 255). This inducible response to DNA damage, called the SOS response by Miroslav Radman (262), is best demonstrated by the effect of split-dose DNA damaging treatments, during which repair-proficient cells show better survival after a particular dose of DNA damaging treatment if the treatment is delivered in several sub-doses separated by short time intervals (77, 277).…”
Section: Evolution Versus Survivalmentioning
confidence: 99%
“…It is well known that treatment of cells with one DNA damaging agent, followed by incubation in growth conditions, makes them better prepared to repair DNA lesions from subsequent exposures to different DNA damaging treatments (216, 255). This inducible response to DNA damage, called the SOS response by Miroslav Radman (262), is best demonstrated by the effect of split-dose DNA damaging treatments, during which repair-proficient cells show better survival after a particular dose of DNA damaging treatment if the treatment is delivered in several sub-doses separated by short time intervals (77, 277).…”
Section: Evolution Versus Survivalmentioning
confidence: 99%
“…a1 (1978) reported the equivalent repair ability in E. coli B,, and B,-, using a D N A unwinding technique. Pollard and Fugate (1978) also reported that E. coli B$-, is able to repair SSB. It is interesting to note that our result on 5, for E. coli B,-, and B,, is close to the experimental one by Ahnstrom et al Town e?…”
Section: Resultsmentioning
confidence: 95%
“…a1 (1978) reported the equivalent repair ability in E. coli B,, and B,-, using a D N A unwinding technique. Pollard and Fugate (1978) also reported that E. coli B$-, is able to repair SSB. It is interesting to note that our result on 5, for E. coli B,-, and B,, is close to the experimental one by Ahnstrom et al…”
Section: The Large Value Of ( U ~) ~/ ( ~T ~) ~~mentioning
confidence: 95%